Impending Carotid Blowout Stabilization Using an LT-D Tube - G. Desuter; A. Gregoire; Q. Gardiner; P. M. Francois (Case Reports in Otolaryngology)
Adequate stabilization of a patient presenting with a carotid blowout is one of the most challenging issues an on-call ENT surgeon can be confronted with. Reducing the bleeding and securing the airway are essential before more definitive management. We present the case of a 72-year-old patient with head and neck cancer who arrived at the emergency room with a carotid blowout and who was successfully stabilized using a King LT-D ventilation tube.